2014
DOI: 10.1074/jbc.m113.534578
|View full text |Cite
|
Sign up to set email alerts
|

Linker Length Matters, Fynomer-Fc Fusion with an Optimized Linker Displaying Picomolar IL-17A Inhibition Potency

Abstract: Background: IL-17A is a proinflammatory cytokine involved in various inflammatory diseases.Results: Potent IL-17A inhibitors were generated by fusing human Fyn SH3 domain derivatives (Fynomers) to the Fc part of an antibody.Conclusion: The linker length between the Fc part and the binding domain influences significantly the potency of Fc fusion proteins.Significance: Fynomers represent a promising class of therapeutic proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Therefore, we expect that tumor independent T cell activation and cytokine release-related syndromes induced by COVA420 through cross-linking of T cells with FcR-bearing accessory cells is unlikely to impede further development of COVA420. As the Fynomer technology offers a broad range of formatting flexibility [20], one could consider the possibility to generate scFv and/or Fab-based Fynomer fusions in order to further minimize the risk of cytokine release-related syndromes upon administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we expect that tumor independent T cell activation and cytokine release-related syndromes induced by COVA420 through cross-linking of T cells with FcR-bearing accessory cells is unlikely to impede further development of COVA420. As the Fynomer technology offers a broad range of formatting flexibility [20], one could consider the possibility to generate scFv and/or Fab-based Fynomer fusions in order to further minimize the risk of cytokine release-related syndromes upon administration.…”
Section: Discussionmentioning
confidence: 99%
“…Fynomers are small (6 kDa) engineered binding proteins that are derived from the SH3 domain of the Fyn kinase [16][17][18][19][20][21]. Fynomers can be genetically fused to different termini of antibodies resulting in bispecific proteins, termed FynomAbs, with different architecture, depending on the Fynomer fusion site.…”
Section: Introductionmentioning
confidence: 99%
“…into C57BL/6 mice. Serum concentrations after 10 minutes, 6, 24, 48, 96, 120, 144, and 168 hours were determined by ELISA on immobilized HER2 (18).…”
Section: In Vivo Tumor Xenograft and Pharmacokinetic Studiesmentioning
confidence: 99%
“…Furthermore, in the same study it has been shown that in a mouse model of acute inflammation, the most potent 2C1-Fc fusion protein was able to efficiently inhibit IL-17A in vivo. According to these evidences, Fynomer-Fc fusion proteins represent new drug candidates for the treatment of IL-17A mediated inflammatory conditions including psoriasis [89].…”
Section: Bi-specific Monoclonal Antibodiesmentioning
confidence: 99%